2000
DOI: 10.1080/10473289.2000.10464003
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Catalytic Oxidation of Benzene,n-Hexane, and Emission Gas from a Refinery Oil/Water Separator over a Chromium Oxide Catalyst

Abstract: With the advances made in the past decade, catalytic incineration of volatile organic compounds (VOCs) has become the technology of choice in a wide range of pollution abatement strategies. In this study, a test was undertaken for the catalytic incineration, over a chromium oxide (Cr 2 O 3 ) catalyst, of n-hexane, benzene, and an emission air/vapor mixture collected from an oil/water separator of a refinery. Reactions were carried out by controlling the feed stream to constant VOC concentrations and temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 24 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…However, in some cases, the power-law model was found to be enough to represent catalytic combustion of VOCs. Wang and Chou demonstrated that a first-order equation with respect to VOC concentration and an Arrhenius temperature dependence of the kinetic constant were adequate to describe catalytic combustion of benzene and hexane in air over Cr 2 O 3 catalyst [32]. Miranda et al reported that power-law expression provided fairy good fits for oxidation of trichloroethene over metal oxide catalysts [33].…”
Section: Power-law Modelmentioning
confidence: 98%
“…However, in some cases, the power-law model was found to be enough to represent catalytic combustion of VOCs. Wang and Chou demonstrated that a first-order equation with respect to VOC concentration and an Arrhenius temperature dependence of the kinetic constant were adequate to describe catalytic combustion of benzene and hexane in air over Cr 2 O 3 catalyst [32]. Miranda et al reported that power-law expression provided fairy good fits for oxidation of trichloroethene over metal oxide catalysts [33].…”
Section: Power-law Modelmentioning
confidence: 98%
“…The range of the reaction activation energies has been taken from the literature. Supposing that the main reaction is a catalytic oxidation or a combustion of paraffin, the activation energy varies between 50 and 120 kJ/mol, corresponding to γ 1 ranging from 10 to 20. The values of γ 2 and γ 3 can be estimated from 10 to 30 for a catalytic combustion, for catalytic dehydrogenations, , and for catalytic hydrogenations . The simulations led in the framework of this paper concern two values of the Thiele criteria: φ NW = 10 is typical for a reaction conducted under strong diffusional limitations.…”
Section: Simulationmentioning
confidence: 99%